A Collaborative Governance Model for Nickel Resource Management in Industrial Areas in Indonesia - Buhari Buhari; An Nisa Dwi Oktaviani; Jauchar Jauchar (Jurnal Kajian dan Penelitian Umum, 2026)
This study examines collaborative governance-based nickel resource management in nickel industrial areas in Indonesia. Nickel is positioned as a strategic commodity in downstreaming, the energy transition, and the electric vehicle supply chain. However, its management faces challenges related to data transparency, inter-agency coordination, licensing accountability, environmental monitoring, and public participation. Using a qualitative approach through document study, this research analyzes regulations, government reports, scholarly articles, and official sources related to nickel governance. The findings indicate that nickel management involves the central government, local governments, industry actors, investors, local communities, academics, and supervisory institutions; however, the relationships among these stakeholders remain largely hierarchical. The proposed model emphasizes area-based collaborative forums, data integration and supply chain traceability, area-based socio-environmental monitoring, meaningful community participation, and equitable benefit sharing. Collaborative governance is therefore necessary to ensure that nickel downstreaming generates not only economic value but also inclusive, accountable, and responsive social and ecological sustainability for producing regions, workers, communities, and future generations.